Motion Regimes during Vertical Continuous Casting with Open and Closed Levels - E. B. Demchenko (Наука и техника)
The paper gives description of casting motion regime in the process of vertical continuous casting with open and closed levels. Correct selection of the regime significantly ensures stability and quality of the produced castings.Analysis of the factors that make it possible to determine parameters of casting motion regimes is given in the paper. The selection of the regimes is carried out on the basis of stability conditions of the casting process.